Peningkatan Hasil Belajar Siswa Melalui Pembelajaran Jigsaw pada Materi Pendidikan Agama Islam - Pakih, Hoirul (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The learning models studied are the jigsaw type cooperative learning model and the expository (lecture) learning model. This research was conducted to determine whether or not there is an influence of the learning model on students' Islamic Religious Education learning outcomes. It is hoped that this will be able to help in the world of learning in relation to the contribution of thought in the form of research results. So it is hoped that with the results of this research innovation in the world of learning will be better and can improve Islamic Religious Education learning outcomes. The general aim of the research is to improve student learning outcomes in Islamic Religious Education subjects through the Jigsaw cooperative learning model specifically to: Improve student learning outcomes, Improve effective, efficient and meaningful learning processes, Increase student interest in learning, Improve the learning process fun and improve teacher professionalism. The research method used is qualitative research, while the type and research approach used in this research is Classroom Action Research. This jigsaw type learning model is described as an effort to create main goals and shared tasks for students, where each student collaborates positively and each member is responsible for studying certain problems from the material provided and conveying this material to other group members